2011
DOI: 10.7498/aps.60.034215
|View full text |Cite
|
Sign up to set email alerts
|

Numeric simulation of the diffraction pattern of zigzag grating

Abstract: The zigzag grating is one of the newly proposed optical dispersive elements which has an excellent diffraction characteristics and has important applications in the spectrum measurement and analysis. The simulation results of the diffraction pattern of the zigzag grating for X ray are presented using a new numerical method based on the convolution theorem, and comparison of its diffraction pattern with those of the traditional grating and sinusoidal grating are studied. It is seen from the results that all hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Based on the STG theory, Cao et al have proposed several types of binary sinusoidal transmission gratings [7][8][9][10][11][12][13][14][15] since 2007. All these binary sinusoidal gratings with nonharmonic diffraction are composed of lots of small size units or complicated structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the STG theory, Cao et al have proposed several types of binary sinusoidal transmission gratings [7][8][9][10][11][12][13][14][15] since 2007. All these binary sinusoidal gratings with nonharmonic diffraction are composed of lots of small size units or complicated structures.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report random position rectangle grating (RPRG) which is designed to overcome these disadvantages. The fabrication of RPRG is much easier than the binary sinusoidal gratings mentioned above [7][8][9][10][11][12][13][14][15] while the property of high-order diffraction restraint is kept. Its 1st-order theoretical absolute diffraction efficiency is as high as 4.1%, far above all binary sinusoidal transmission gratings.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this theory, some binary single order diffraction gratings have been developed. [12][13][14][15][16][17][18][19][20][21] A quantum-dot-array diffraction grating (QDADG) has been reported by Wang et al, [12,13] and in its design a great many quantum dots are distributed on a substrate, which obey the sinusoidal function. A QDADG for visible light has been fabricated and the experiment has shown that higher-order diffractions disappear as predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The shortages of QDADG and QSTG are that each of them needs an underlayment since they do not stand themselves, while most underlayment absorbs X-ray seriously. Zang et al [17,18] presented a zigzag transmission grating composed of a series of zigzag-profiled strips, which can also achieve the purpose of single order diffraction. But the zigzag-profiled strips demand an extremely critical nanofabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Donoho and Johnstone proposed the Wavelet Threshold Denoising Method and also gave the threshold value formula, which was applied to a variety of noise reductions and achieved great success. But this general threshold has serious "over-shrinked" tendency for wavelet coefficients, especially the higher frequency part in the useful signal is often treated as noise for removal [3][4] . To solve this problem, this article proposes the Gradient Threshold Denoising Method based on the autocorrelation analysis of wavelet detail coefficient, and describes the determination of the wavelet decomposition layers and conducts experimental study.…”
mentioning
confidence: 99%